Migration Patterns of Sumenep People to Saudi Arabia and Malaysia and Its Impact on Social Economic Institution in the Place of Origin - Surjono, Gunanto; Usman, Sunyoto; Hargo Yuwono, Pujo Semedi (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is done to know migration patterns of Sumenep people, Madura to Saudi Arabia and Malaysia from their subjective meaning, and its impact on local social economy in the place of origin. Methodological paradigm of this research is humanism. Data resources are 788 files of ex-migrant workers (either regular or non-regular) in Sumenep Regency, Madura, East Java Province. Data are gathered through documentary analysis compilation, then being told â€œlivelyâ€ through interview with 48 informants choosen from migrant workers, and focus group discussion. Data also enriched through non-participant observation at several migrant workers hubs in Sumenep Regency, and analyzed through qualitative-descriptive technique. The results shows that migrant workers can be divided in three main patterns, namely regular(managed by PPTKIS), non-regular and non-regular absolute (managed by indivudual mediator, tekong). Their choice based on the reasons that regular pattern through PPTKIS needs much money, have to go through intricate red-tape, and tends formal in its social relation, while non-regular pattern does not need much money, having familiar and emotional social relation, quick process, and arranged by their closed family or friend. Although, according to article 4 juncto article 102 of the Indonesian Human Resources (TKI) Regulation No 39, 2004 stipulating that anyone violates the regulation will be fined 2-15 million rupiah or jailed for 2-10 years. But the regulation still does not discourage Sumenep migrant workers to choose non-reguler pattern, as in practice both regular and non-regular remain indifferent. The other result show that the impact of Sumenep migrant workers can activate local social and economy through the remitance they spend in consumtive and business activities, some also donated to infrastructures development, sort of school, lanes, and religious building.